Discurso parlamentar: estratégias de retextualização - Oliveira, Maria Rodrigues de (2009)
This dissertation deals with the retextualization of parliamentary debates and intends to map changes introduced by retextualizers during the transformation of parliamentary oral speeches into written texts, as well as to analyze these changes in order to understand their implications for the meaning of the text. The research is relevant because parliamentary debates contribute to the validation of Executive and Legislative acts. Translated from oral into written language, these speeches make up the annals of legislative chambers, and so become essential historic records, and can be ordered by the Courts as evidence in legal proceedings. The retextualization of these speeches, having in mind the importance of what is said in plenary sessions, should excel in their fidelity to the speaker s words and respect for his style. However, these two requirements are not always met because there are changes in the retextualization process that distance the source text (speech) from the secondary text (written). This research is based primarily on studies located in the field of Textual Linguistics and Conversation Analysis and its corpus consists of extracts from five Guarulhos City Chamber (São Paulo State) ordinary sessions that took place between 2001 and 2007. The results indicate that deletions, insertions and substitutions are the main changes made by retextualizers and that those affect the style, the speakers words and the meaning of the text